Fermented Oyster (Crassostrea gigas) Extract Cures and Prevents Prednisolone-Induced Bone Resorption by Activating Osteoblast Differentiation - Ilandarage Menu Neelaka Molagoda; Athapaththu Mudiyanselage Gihan Kavinda Athapaththu; Eui Kyun Park; Yung Hyun Choi; You-Jin Jeon; Gi-Young Kim (Foods, 2022)
Osteoporosis is a bone resorptive disease characterized by the loss of bone density, causing an increase in bone fragility. In our previous study, we demonstrated that gamma aminobutyric acid-enriched fermented oyster (Crassostrea gigas) extract (FO) stimulated osteogenesis in MC3T3-E1 preosteoblast cells and vertebral formation in zebrafish. However, the efficacy of FO in prednisolone (PDS)-induced bone resorption remains unclear. In this study, we evaluated the osteogenic potential of FO in MC3T3-E1 preosteoblast cells and zebrafish larvae under both PDS-pretreated and PDS-post-treated conditions. We found that FO recovered osteogenic activity by upregulating osteoblast markers, such as alkaline phosphatase (ALP), runt-related transcription factor 2, and osterix, in both PDS-pretreated and post-treated MC3T3-E1 osteoblast cells and zebrafish larvae. In both conditions, PDS-induced decrease in calcification and ALP activity was recovered in the presence of FO. Furthermore, vertebral resorption in zebrafish larvae induced by pretreatment and post-treatment with PDS was restored by treatment with FO, along with the recovery of osteogenic markers and downregulation of osteoclastogenic markers. Finally, whether FO disturbs the endocrine system was confirmed according to the Organization for Economic Cooperation and Development guideline 455. We found that FO did not stimulate estrogen response element-luciferase activity or proliferation in MCF7 cells. Additionally, in ovariectomized mice, no change in uterine weight was observed during FO feeding. These results indicate that FO effectively prevents and treats PDS-induced osteoporosis without endocrine disturbances.